Bi-functional ZnO nanoparticles as a reusable SERS substrate for nano-molar detection of organic pollutants - Majee B.P.; Bhawna; Mishra A.K. (My University, 2025)
In order to identify the quality of water, detection of organic pollutants at very low concentrations is needed. In this work, hydrothermally grown ZnO nanoparticles (NPs) were used as a SERS active substrate for the detection of nano-molar concentration (10-9 M) of Methylene Blue (MB) and Methyl Orange (MO), which is the best known detection limit for any pristine metal oxide nanoparticles as a SERS substrate to detect organic pollutants. Additionally, self cleaning property of used SERS substrate was demonstrated under UV light irradiation in aqueous medium for the reusability of SERS substrate. These cleaned ZnO based SERS substrates were reused to detect the organic pollutant with repeated detectability. Hence, bi-functional behaviour of ZnO NPs is demonstrated in the present work by detection of organic pollutant using ZnO based SERS substrate and self cleaning of SERS substrate for its reusability. © 2020 IOP Publishing Ltd.